Designing an Integrated Architecture for Network Content Security Gateways. - Ying-Dar Lin; Chih-Wei Jan; Po-Ching Lin; Yuan-Cheng Lai (Computer (00189162), 2006)
The article presents a discussion about designing an integrated architecture for network content security gateways. The installation of multiple network security products in detecting and blocking viruses, spam, and other intrusions indicates overhead in interprocess communications and user space interactions. These open source content security packages include, snort, ClamAV, SpamAssassin, amavisd, and DansGuardian. The problems to be addressed in designing these security gateways are architectures being loosely or tightly integrated.